Association of the vitamin D receptor gene start codon Fok I polymorphism with calcium oxalate stone disease - Chen, W.‐C.; Chen, H.‐Y.; Lu, H.‐F.; Hsu, C.‐D.; Tsai, F.‐J. (BJU international, 2001)
Objective To assess the use of Fok I polymorphism (the most frequent polymorphism, at the start codon of the vitamin D receptor gene, VDR) as a convenient genetic marker in identifying the cause of urolithiasis. Patients, subjects and methods A normal control group of 90 healthy subjects and 146 patients with calcium oxalate stones were examined. Using polymerase chain reaction (PCR)‐based restriction analysis, the relationship between Fok I polymorphism and urolithiasis was evaluated. An unexcisable length of 265 bp was identified (allele CC) and two fragments (169 bp and 96 bp) identified as excisable lengths (allele TT). Results There was a statistically significant difference between the groups (chi‐square test, P < 0.05) for the genotype of the VDR Fok I start codon polymorphism. The odds ratio (95% confidence interval) for the C allele in those at risk of stone disease was 1.672 (1.149–2.432). Conclusions These results suggest that the VDR Fok I start codon polymorphism may be a good candidate for a genetic marker in calcium oxalate stone disease.